Lake Sturgeon, Lake Whitefish, and Walleye Egg Deposition Patterns with Response to Fish Spawning Substrate Restoration in the St. Clair–Detroit River System. Issue 1 (26th February 2018) - Fischer, Jason L.; Pritt, Jeremy J.; Roseman, Edward F.; Prichard, Carson G.; Craig, Jaquelyn M.; Kennedy, Gregory W.; Manny, Bruce A.
Abstract: Egg deposition and use of restored spawning substrates by lithophilic fishes (e.g., Lake Sturgeon Acipenser fulvescens, Lake Whitefish Coregonus clupeaformis, and Walleye Sander vitreus ) were assessed throughout the St. Clair–Detroit River system from 2005 to 2016. Bayesian models were used to quantify egg abundance and presence/absence relative to site‐specific variables (e.g., depth, velocity, and artificial spawning reef presence) and temperature to evaluate fish use of restored artificial spawning reefs and assess patterns in egg deposition. Lake Whitefish and Walleye egg abundance, probability of detection, and probability of occupancy were assessed with detection‐adjusted methods; Lake Sturgeon egg abundance and probability of occurrence were assessed using delta‐lognormal methods. The models indicated that the probability of Walleye eggs occupying a site increased with water velocity and that the rate of increase decreased with depth, whereas Lake Whitefish egg occupancy was not correlated with any of the attributes considered. Egg deposition by Lake Whitefish and Walleyes was greater at sites with high water velocities and was lower over artificial spawning reefs. Lake Sturgeon eggs were collected least frequently but were more likely to be collected over artificial spawning reefs and in greater abundances than elsewhere. Detection‐adjusted egg abundances were not greater over artificial spawning reefs, indicating that these projects may not directly benefit spawning Walleyes and Lake Whitefish. However, 98% of the Lake Sturgeon eggs observed were collected over artificial spawning reefs, supporting the hypothesis that the reefs provided spawning sites for Lake Sturgeon and could mitigate historic losses of Lake Sturgeon spawning habitat.